Recent advances on second-order NLO materials based on metal iodates - Hu, Chun-Li; Mao, Jiang-Gao (Coordination chemistry reviews, 2015)
Metal iodates with a lone-pair containing I(V) in an asymmetric coordination geometry can form a diversity of unusual structures, including non-centrosymmetric (NCS) or polar structures with promising second order NLO properties. They have wide transparent wavelength regions, large second-harmonic-generation (SHG) coefficients and high optical-damage thresholds as well as good thermal stability. In this review, the structures and second-order NLO properties of metal iodates will be discussed. The synthetic routes for new SHG materials based on metal iodates include the condensation of iodate groups into SHG active polyiodate anions, the introduction of other lone pair containing cations, octahedrally coordinated d0 transition-metal cations and the d8-transition metal ion with a square planar TMO4 geometry into the metal iodate systems. •Recent advances on second order NLO materials based on metal iodates are reviewed.•Under suitable conditions, IO3 and IO4 groups are able to be polymerized.•Combination of two types of lone pair cations afforded many new polar materials.•The d0-TMO6 octahedra can be combined with iodate groups to form new SHG compounds.•Square planar TMO4 units can be used to form polar metal iodates. Metal iodates with a lone-pair containing I(V) in an asymmetric coordination geometry can form a diversity of unusual structures, including non-centrosymmetric (NCS) structures with promising second-order nonlinear optical (NLO) properties. They have wide transparent wavelength regions (0.4–12μm), large second harmonic generation (SHG) coefficients (>10×KDP for many iodates) and high optical-damage thresholds (4–50GWcm−2) as well as good thermal stability (usually >400°C). In this review, the structures and second-order NLO properties of metal iodates will be discussed. Under reaction media with a high concentration of iodic acid, the iodate groups can be condensed into binuclear or polynuclear iodate anions, these compounds are able to display large SHG responses. The introduction of other lone pair containing cations into the iodate system is also an effective strategy to design new NCS materials. The combination of d0 transition-metal cations with iodate groups afforded a large number of NCS metal iodates with anionic structures ranging from 0D clusters, 1D chains, 2D layers to 3D networks. These NCS materials can display excellent second-order NLO properties when the polarizations from both types of the asymmetric units are aligned properly. As for the iodates of d8-transition metal ion with a square planar TMO4 geometry, the cis TM(IO3)4 unit in which the four iodate groups are located at the same side of the TMO4 plane favors the formation of NCS structures whereas the trans- one in which the four iodate groups being located at both sides of the TMO4 square plane prefers to a centrosymmetric structure. NCS structures with good SHG properties can also be found in other mixed metal iodate systems.